Tidal Disruption of Planetesimals from an Eccentric Debris Disk Following a White Dwarf Natal Kick - Tatsuya Akiba; Selah McIntyre; Ann-Marie Madigan (The Astrophysical Journal Letters, 2024)
The surfaces of many white dwarfs are polluted by metals, implying a recent accretion event. The tidal disruption of planetesimals is a viable source of white dwarf pollution and offers a unique window into the composition of exoplanet systems. The question of how planetary material enters the tidal disruption radius of the white dwarf is currently unresolved. Using a series of N -body simulations, we explore the response of the surrounding planetesimal debris disk as the white dwarf receives a natal kick caused by anisotropic mass loss on the asymptotic giant branch. We find that the kick can form an apse-aligned, eccentric debris disk in the range 30–240 au, which corresponds to the orbits of Neptune, the Kuiper Belt, and the scattered disk in our solar system. In addition, many planetesimals beyond 240 au flip to counterrotating orbits. Assuming an isotropic distribution of kicks, we predict that approximately 80% of white dwarf debris disks should exhibit significant apsidal alignment and a fraction of counterrotating orbits. The eccentric disk is able to efficiently and continuously torque planetesimals onto radial, star-grazing orbits. We show that the kick causes both an initial burst in tidal disruption events as well as an extended period of 100 Myr where tidal disruption rates are consistent with observed mass accretion rates on polluted white dwarfs.